2018
DOI: 10.1111/aab.12450
|View full text |Cite
|
Sign up to set email alerts
|

Wheat's wild relatives vary in their response to nitrogen and ozone

Abstract: The wild relatives of bread wheat (Triticum aestivum) are valued by plant breeders for their genetic diversity. However, increasing levels of nitrogen (N) deposition and ground-level ozone (O 3 ) threaten plant biodiversity in the Mediterranean and Near-East, a hotspot for many crop wild relatives. Knowledge of the effect of these air pollutants in combination is still limited, but early indications are that effects vary depending on the level of pollutants, and on the sensitivity of the species to N and O 3 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This is contrary to previous assessments of the ozone sensitivity of Ae. tauschii using young plants in a short ozone exposure during the vegetative stage [32,33]. The previous studies suggested that Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to previous assessments of the ozone sensitivity of Ae. tauschii using young plants in a short ozone exposure during the vegetative stage [32,33]. The previous studies suggested that Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of the ozone sensitivity of some of the close wild relatives of wheat have been made previously in short term experiments [32,33], with young plants (3–6 weeks old) receiving 3 weeks of ozone fumigation at 100 ppb concentrations. Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N fertilisation can profoundly alter plant growth, physiology, and productivity, all of which may shape the associated soil microbial community (Eastman et al, 2021; Zhang et al, 2018). Prior studies of O 3 × N interactions have primarily focused on aboveground effects and have yielded contradictory results, with some authors having reported that N addition can reverse the negative impact of O 3 exposure (Handley & Grulke, 2008; Mills et al, 2016), whereas others observed the opposite effect (Azuchi et al, 2014; Brewster et al, 2018) or detected no relationship between these variables (Feng, Shang, Li, et al, 2019; Harmens et al, 2017; Li et al, 2020). How soil microbial communities respond to O 3 and N addition thus remains to be clarified, and as such, further analyses of ecosystem responses and O 3 pollution feedback in an N‐enriched biosphere are warranted.…”
Section: Introductionmentioning
confidence: 99%